Amphicercidus (Hemiptera, Aphidinae, Macrosiphini) species in China: two synonyms and two new records - Ying Xu; Jing Chen; Bakhtiyor Rustamovich Kholmatov; Li-Yun Jiang; Ge-Xia Qiao (ZooKeys)
Amphicercidus Oestlund, 1923 is distinguished from other aphid genera by a body in life heavily covered with white wax powder, antennal segment III rather long and with numerous secondary rhinaria, body dorsal setae long and pointed, the second hind tarsal segment longer than the ultimate rostral segment, siphunculi as long stout cylinders, and cauda broad and short. Based on the examination of Chinese specimens, two species were found to be synonyms of Amphicercidus japonicus (Hori, 1927): Amphicercidus forsythiae Zhang, Zhong & Zhang, 1992, syn. nov. and Amphicercidus sinilonicericola Zhang, 1980, syn. nov. Additionally, Amphicercidus pulverulens (Gillette, 1911) and Amphicercidus tuberculatus David, Narayanan & Rajasingh, 1971 are reported here as new records for China. Additionally, Lonicera (Caprifoliaceae) is a new host plant record for Amphicercidus pulverulens. The DNA barcodes for A. japonicus, A. pulverulens and A. tuberculatus have been obtained, with the barcodes of A. pulverulens and A. tuberculatus being acquired for the first time. Keys to Chinese species in this genus are presented.